Pengaruh Kinerja Keuangan Daerah Terhadap Pertumbuhan Ekonomi - Nisak, Zikratun; Rasyidin, Muhammad; Rizkina, Azka; Rizal, Muhammad (TIN: Terapan Informatika Nusantara, 2024)
This study seeks to evaluate the impact of regional financial independence ratios, PAD effectiveness ratios, and regional financial efficiency ratios on economic growth in Aceh Province. The research focuses on financial performance data, including PAD, regional expenditures, and the APBD, along with economic growth metrics. The location of the study is Aceh Province, utilizing secondary data from 1993-2022 obtained from BPS Aceh Province. The findings indicate that the regional financial independence ratio does not significantly affect economic growth in Aceh Province, due to inefficiencies in the use of regional financial resources, such as fund mismanagement or unproductive investments. Similarly, the PAD effectiveness ratio shows no impact on economic growth, attributed to the lack of income source diversification, with many regions relying predominantly on specific sectors like property taxes or hotel and restaurant taxes. Conversely, the regional financial efficiency ratio positively influences economic growth, as efficient fund utilization enhances infrastructure and education availability, directly boosting labor productivity and regional competitiveness.